Spouse Participation in Prevention and Intervention of Postpartum Depression: Roles, Strategies, and Interventions - Hou Yongmei (Disease and Health: Research Developments Vol. 1, 2024)
Objective: The primary objective of this study is to explore the mutual influence of postpartum depression (PPD) between mothers and their spouses, as well as the role of spouse participation in preventing and managing PPD in mothers. Methods: A literature search was used to organize and analyze 64 articles, elaborating on the correlation between postpartum depression in mothers and their spouses, the role of spouses’ participation in preventing and managing postpartum depression in mothers, and analyzing several commonly used methods for spouses to participate. Results: The incidence of PPD among mothers ranged from 3.1% to 20.4%, with an average incidence of 16.7%, and the incidence of PPD in maternal spouses ranged from 3.4% to 14.7%, with an average incidence of 10.4%. There is a significant correlation (r=0.20-0.42, all P<0.05) between PPD in mothers and that in spouses. Spouses participating in the prevention and intervention of PPD can effectively promote mutual understanding between fathers and mothers, improve their marital relationships, reduce the level of depression in fathers and mothers, lower the incidence of PPD, and promote postpartum recovery and physical development of infants. Conclusion: Spouse participation is one of the effective ways to prevent and intervene in PPD, with good short-term effects. We need to conduct additional large sample multicenter follow-up surveys or randomized controlled studies to confirm its long-term effects.